Maternal smoking during pregnancy and childhood overweight and fat distribution: the KOALA Birth Cohort Study. Issue 1 (30th January 2013) - Timmermans, S. H.; Mommers, M.; Gubbels, J. S.; Kremers, S. P. J.; Stafleu, A.; Stehouwer, C. D. A.; Prins, M. H.; Penders, J.; Thijs, C.
Summary What is already known about this subject There is an association between maternal smoking during pregnancy and higher body mass index (BMI) and overweight in childhood. What this study adds The association between maternal smoking during pregnancy and childhood overweight develops with age, starting with a lower birth weight, followed by weight catch‐up in the first year after birth, finally leading to overweight at school age. Children of mothers who had smoked during pregnancy had a higher risk of exceeding the 85th percentile of BMI, waist circumference and total skinfold thickness at school age. Background Maternal smoking during pregnancy is associated with childhood overweight, but the association with fat distribution is not clear. Objective To explore the longitudinal association between smoking during pregnancy and childhood overweight and fat distribution. Methods In the KOALA Birth Cohort Study, repeated questionnaires were administered to 2698 mother–child pairs, including questions on smoking at 14 and 34 weeks of pregnancy. Main outcomes were birth weight, weight gain in the first year, body mass index (BMI) z‐scores and overweight (BMI ≥85th percentile) at 1, 2, 4–5 and 6–7 years (n = 1730) and waist circumference and four skinfold thicknesses measured at home visits at age 6–7 years in a subgroup (n = 418). We used multivariable linear and logistic regression, with generalized estimating equations (GEE) for repeated measurements. Results Maternal smoking was associated with lower birth weight, higher weight gain in the first year and increasing overweight after infancy (change with age P = 0.02 in the GEE). Maternal smoking vs. non‐smoking during pregnancy was associated with a higher risk of the child exceeding the 85th percentile of BMI (adjusted odds ratio [aOR] 3.72; 95% CI 1.33–10.4), waist circumference (aOR 2.65; 95% CI 1.06–6.59) and sum of skinfold thicknesses (aOR 4.45; 95% CI 1.63–12.2) at the age of 6–7 years. Conclusions Maternal smoking during pregnancy is associated with lower birth weight, weight catch‐up and development of overweight into childhood.